2019
DOI: 10.1111/trf.15415
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and behavioral characteristics associated with blood donation in the United States: a population‐based study

Abstract: BACKGROUND Contemporary population‐based data on characteristics associated with blood donation in the United States (U.S.) are limited. STUDY DESIGN AND METHODS A cross‐sectional analysis was performed among 28,739 persons aged 18 years and older who participated in the 2016 National Health Interview Survey, a household survey of the noninstitutionalized U.S. civilian population. Analyses were weighted and accounted for the complex survey design. Adjusted prevalence ratios (aPR) were estimated by multivariabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 45 publications
2
50
1
Order By: Relevance
“…In the future, efforts to nd donors should be based both on providing them with appropriate knowledge and on shaping favorable attitudes. Other factors should also be taken into account because, as is known, blood donation rates are lower for some minority groups due to factors such as fear, cultural, ethnic and religious beliefs and distrust of medical institutions 22,23 . It may be suspected that similar factors may affect also potential CP donors.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, efforts to nd donors should be based both on providing them with appropriate knowledge and on shaping favorable attitudes. Other factors should also be taken into account because, as is known, blood donation rates are lower for some minority groups due to factors such as fear, cultural, ethnic and religious beliefs and distrust of medical institutions 22,23 . It may be suspected that similar factors may affect also potential CP donors.…”
Section: Discussionmentioning
confidence: 99%
“…Other designs/populations may be biased in either direction, more frequently towards underestimating seroprevalence. [19][20][21][22][23][24][25][26] One study (LA County) 12 with very low IFR was excluded with the justification that it 'explicitly warned against using its data to obtain an IFR'; as a co-investigator of the study, both myself and my colleagues are intrigued at the rationale for exclusion; in the publication of the study in JAMA, 12 we did list limitations and caveats, as it is appropriate for any seroprevalence study to do; excluding studies that are honest to discuss limitations would keep only the worst studies that discuss no limitations. Two other studies with low IFR were excluded as well.…”
Section: Information Usedmentioning
confidence: 99%
“…In countries with large shares of minorities (eg USA and UK), minorities are markedly under-represented among blood donors. 23,24 For example, in the USA, donation rates are 37%-40% lower in blacks and Hispanics versus whites 23 and in the UK, donation rates range from 1.59 per 1000 among Asian Bangladeshi origin, compared to 22.1 per 1000 among white British origin. 24 These minorities were hit the most by COVID-19.…”
Section: Blood Donorsmentioning
confidence: 99%
“…It has previously been shown that these groups contain disproportionate numbers of people that are young, White, college graduates, employed, physically active, and never-smokers. 38,39 Investigators using these proxy sampling frames should ensure robust correction for demographic differences or consider incorporating a correction factor (1.67x) to yield more representative estimates. Our systematic review is the largest synthesis of SARS-CoV-2 serosurveillance data to date.…”
Section: Seroprevalence To Cumulative Incidence Ratiomentioning
confidence: 99%